Tug-Barge Operating Costs based on Charterer Versus Ownership Perspective. A Case Study: Nickel Ore Transport Boenaga-Fatufia Route - Sitorus, Chris Jeremy Verian; Idrus, Misliah; Chaerunnisa, Andi Sitti (EPI International Journal of Engineering, 2023)
The Tug-barge operating costs for nickel ore transhipment at Boenaga-Fatufia are based on charter and shipowner. A comprehensive study on Tug-barge investment feasibility needs to focus on the most profitable option. This study aims to determine the feasibility of investing in a Tug-barge, considering a charter Tug-barge with shipowner (newbuilding tug-barge and secondhand Tug-barge is feasible compared to a new building Tug-barge and charter Tug-barge. The highest NPV is for the secondhand Tug-barge, IDR 18.642.830.529; rhe secondhand Tug-barge also gas the highest IRR value of 20%. The secondhand Tug-barge has the fastest Payback Period, Which is 4.18 years.